2015
DOI: 10.1021/acs.jpcb.5b08168
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Anion Hydrogen Bonding Dynamics in Aqueous Solution

Abstract: The dynamic nature of hydrogen bonding between a molecular anion, selenocyanate (SeCN(-)), and water in aqueous solution (D2O) is addressed using FT-IR spectroscopy, two-dimensional infrared (2D IR) vibrational echo spectroscopy, and polarization selective IR pump-probe (PSPP) experiments performed on the CN stretching mode. The CN absorption spectrum is asymmetric with a wing on the low frequency (red) side of the line in contrast to the spectrum in the absence of hydrogen bonding. It is shown that the red wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 49 publications
6
84
1
Order By: Relevance
“…1,12,85 2D IR would be highly sensitive to such solvent shell dynamics. [57][58][59] The fast β-process usually appears on a few picosecond time scale with a weak temperature dependence as is observed for the 2D IR data, although it also generally appears as a power law in the MCT equations. This is again attributable to the differences in the FFCF from other correlators, and it has been previously demonstrated that a schematic MCT correlator is as capable of describing a multiexponential decay as a power law.…”
Section: Analysis With the Kubo Modelmentioning
confidence: 65%
See 2 more Smart Citations
“…1,12,85 2D IR would be highly sensitive to such solvent shell dynamics. [57][58][59] The fast β-process usually appears on a few picosecond time scale with a weak temperature dependence as is observed for the 2D IR data, although it also generally appears as a power law in the MCT equations. This is again attributable to the differences in the FFCF from other correlators, and it has been previously demonstrated that a schematic MCT correlator is as capable of describing a multiexponential decay as a power law.…”
Section: Analysis With the Kubo Modelmentioning
confidence: 65%
“…This model has had great success in fitting 2D IR data for a variety of systems including organic liquids, water, proteins, liquid crystals, and room-temperature ionic liquids. [55][56][57][58][59][71][72][73][74][75] The multiexponential model was chosen as our starting point, as above T m , these glass forming liquids are simple organic liquids. At these higher temperatures, the CLS(T w ) decay curves for all three samples fit well to biexponential decays.…”
Section: Fitting Procedures and Choice Of Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conformational search has been discussed in the literature. [12] The lowest energy conformer of the literature has been compared with that of our study. Since the literature has not provided the corresponding Cartesian coordinates, we have modelled their stable conformer on the basis of visual orientations.…”
Section: Resultsmentioning
confidence: 99%
“…TKX-50 in recent time followed by many other studies like thermal, compatibility, performance prediction, mechanistic decomposition and computational studies in respect of TKX-50. [9][10][11][12][13][14] ABTOX is a parallel product in the easy one-pot five step synthetic route of TKX-50 starting from glyoxime. Further, its high thermal stability and insensitivity (impact and friction) than TKX-50 prompted us to consider ABTOX for its comparative study with TKX-50.…”
Section: Introductionmentioning
confidence: 99%